Hamlet Underground: Revisiting Shakespeare and Dostoevsky - Thurman, Chris (Multicultural Shakespeare: Translation, Appropriation and Performance, 2018)
This is the first of a pair of articles that consider the relationship between Dostoevsky’s novella Notes from the Underground and Shakespeare’s Hamlet. Acknowledging Shakespeare’s well-known influence on Dostoevsky and paying close attention to similarities between the two texts, the author frames the comparison by reflecting on his own initial encounter with Dostoevsky in David Magarshack’s 1968 English translation. A discussion of previous Anglophone scholarly attempts to explore the resonance between the texts leads to a reading of textual echoes (using Magarshack’s translation). The wider phenomenon of Hamletism in the nineteenth century is introduced, complicating Dostoevsky’s national and generational context, and laying the groundwork for the second article—which questions the ‘universalist’ assumptions informing the English translator-reader contract.